Genome-wide identification of PDX and expression analysis under waterlogging stress exhibit stronger waterlogging tolerance in transgenic Brassica napus plants overexpressing the BnaPDX1.3 gene compared to wild-type plants - Yao, Mingyao; Hong, Bo; Ji, Hongfei; Guan, Chunyun; Guan, Mei (Frontiers in Plant Science, 2025)
The PDX gene is a key gene in the vitamin B6 synthesis pathway, playing a crucial role in plant growth, development, and stress tolerance. To explore the family characteristics of the PDX gene in Brassica napus (B. napus) and its regulatory function under waterlogging stress, this study used five PDX genes from Arabidopsis thaliana as the basis for sequence analysis. Thirteen, eight, and six PDX genes were identified in B. napus, Brassica oleracea (B. oleracea), and Brassica rapa (B. rapa), respectively. Bioinformatics study reveals high conservation of PDX subfamily genes during evolution, and PDX genes in B. napus respond to waterlogging stress.In order to further investigate the effect of the PDX gene on waterlogging tolerance in B. napus, expression analysis was conducted on BnaPDX1.3 gene overexpressing B. napus plants and wild-type plants. The study showed that overexpressing plants could synthesize more VB6 under waterlogging stress, exhibit stronger antioxidant enzyme activity, and have a more effective and stable ROS scavenging system, thus exhibiting a healthier phenotype. These findings suggested that the BnaPDX1.3 gene can enhance the waterlogging tolerance of B. napus, which is of great significance for its response to waterlogging stress. Our study provides a basic reference for further research on the regulation mechanism of the PDX gene and waterlogging tolerance in B. napus.